AUDIT TATA KELOLA TEKNOLOGI INFORMASI PADA PERGURUAN TINGGI SWASTA DI SURAKARTA (Studi Kasus: Politeknik Indonusa Surakarta) - Dwi Iskandar; Kusrini .; M Rudyanto Arief (Politeknik Indonusa Surakarta, 2017)
Their IT governance in higher education can provide one support to determine the benefits and risks that would be obtained. Audit of information technology governance in Politeknik Indonusa Surakarta conducted to assess, ascertain, find out what the cause and provide recommendations on the application of information technology in polytechnics indonusa Surakarta. To evaluate an information technology must use a tool such as the framework and framework used is COBIT 5, because the problem is also related to the management area contained in the framework.In this research for problem resolution will refer to the Standard Framework COBIT 5 with Of Enterprise IT Management of area and more focused on domain MEA (Monitor, Evaluate and Assess) on the control objective is MEA01 - Monitor, Evaluate, and Assess Performance and Conformance. Scope of IT governance is SIAKAD (Sistem Informasi Akademik), SIMANTA (Sistem Informasi Manajemen Tugas Akhir).The study provides, among others, the level of ability (Capability Level) the application of information technology today, obstacles in the implementation of IT, as well as provide recommendations can be given with regard to the use of IT.